Host Selection Behavior of the Green Peach Aphid, Myzus persicae, in Response to Volatile Organic Compounds and Nitrogen Contents of Cabbage Cultivars - Ahmed, Nazeer; Darshanee, Hewa Lunuwilage Chamila; Khan, Imtiaz Ali; Zhang, Zhan-Feng; Liu, Tong-Xian (Frontiers in Plant Science, 2019)
Plants emit volatile organic compounds (VOCs) in response to herbivore attack. VOCs emitted from the Chinese cabbage cultivars in response to the damage by the green peach aphid, Myzus persicae, were unknown. Using a solid-phase microextraction-based headspace collection method, we investigated and compared the emissions of VOCs from seven Chinese cabbage cultivars (Qibao, Qingan 80, Lvlong, Yuanbao, Qingan 70, Jinlv, and Lvqiu 66) in response to M. persicae attack. Our results showed that the VOCs emitted from the cultivars Qingan 80 and Yuanbao differed significantly from the other cultivars in response to the attraction of wingless M. persicae. Most importantly, out of the 27 detected compounds, α-caryophyllene was detected only in Qingan 80 and Qibao, but not in the other five cultivars. Among the compounds detected, 2 green leaf volatiles (GLVs) and 12 terpenes were predominant in all cabbage cultivars. Furthermore, the wingless M. persicae showed preference to Qingan 80 while it had the highest nitrogen content among the tested cultivars. Moreover, we found a remarkable relationship among M. persicae attraction, plant nitrogen content, and total volatile emissions. Nitrogen content of the plants has a significant impact on volatile emission and preference behaviour of M. persicae. Our results indicate that the wingless M. persicae were efficient in their interspecific host selection with an ability to distinguish plant cultivar differences by leaf nitrogen content. This study will be helpful in understanding aphid host selection, and sets a stage to further study the attractant-based integrated aphid management programs.